Foreign Bodies in the External Auditory Canal: An Evaluation of 95 Cases - KARS, Ayhan; ATALAY, Fatma; TOPAL, Kübra (Selcuk University, 2022)
Objective: The purpose of this study was to examine the demographic characteristics, form of presentation to hospital, the ear in which foreign bodies were observed, and the features thereof, in cases of foreign body in the external auditory canal (EAC) treated in our clinic. Materials and Methods: Ninety-five patients presenting to our hospital due to foreign body in the EAC and treated in the Ear, Nose, and Throat (ENT) Clinic were included in the study. Patients’ medical records were examined, and age, sex, type of presentation to hospital, type of foreign body, and the ear involved were recorded. Results: Sixty-eight (71.5%) of the 95 patients were adults aged 20-85, and 27 (28.5%) were children aged 2-17. Fifty-two (54.7%) patients were male and 43 (45.3%) were female. The foreign body was located in the right ear in 47 (49.5%) cases, the left ear in 45 (47.3%), and in both ears in three (3.2%). Twenty-seven (27.6%) of the foreign bodies consisted of cotton swabs, 14 (14.3%) of insects, 13 (13.2%) of beads, 11 (11.2%) of grass pieces. Conclusion: Foreign bodies in the EAC are a frequent problem in ENT practice. In order to avoid complications, foreign bodies should be removed using appropriate techniques and equipment by professional ENT physicians.
Keywords: Dış kulak yolu; KBB uzmanı; erişkin; yabancı cisim; Klinik Tıp Bilimleri; Medicine (General); adult; Clinical Sciences; foreign body; R5-920; external auditory canal; dış kulak yolu; ent specialist; kbb uzmanı; Adult; ENT specialist; external auditory canal; foreign body; yabancı cisim; erişkin; 3. Good health